Application of cell-derived vesicle-based biomimetic drug delivery system in tumor therapy - Mei, Yan; Liu, Maochang; Mei, Meng (Frontiers in Pharmacology, 2025)
Cell-derived vesicles play a crucial role in intercellular information transmission and serve as vital carriers facilitating cell-to-cell communication. These vesicles contain specific biological information from their parental cells, enabling them to transport proteins, cytokines, mRNA, and DNA to other cells or organs. Presently, cell-derived vesicles have extensive application in inhibiting tumor growth and metastasis, as well as in tumor diagnosis and early screening. Numerous studies have highlighted the potential of cell-derived vesicles as drug delivery systems, showcasing advantages such as enhanced biocompatibility, natural active targeting, improved systemic circulation, and greater efficacy compared to conventional drug delivery carriers. In this article, we aim to explore the utilization of cell-derived vesicles as drug delivery systems in tumor therapy, focusing on various drug-loading techniques and analyzing the advantages and characteristics of different types of cell-derived vesicles. Our findings will provide valuable assistance in the development of drug delivery systems based on these vesicles.